Critical Toponymy: Creating Prestigious Spaces Through Using Urban Names - Cetin, Reycan; Senturk, Aylin (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2019)
Place names are important for memory and identity and were researched by many kind of social sciences as history, anthropology, human geography, linguistic. Researches revealed that place names build organic relations with history and culture of the place. 1980s the cultural turn effected researches of place names too, and a critical approach has shown up specially in urban toponymy. First, the critical urban toponymy researches focused on how the urban names were used as a tool to gain political power. In time, considering changes on global economy and its reflections on cities, critical urban toponymy started to think on urban names as economic tools too. Not only the physical space but also urban names became a commodity which can be bought or sale. And also urban names are used to create prestigious urban spaces. This paper aims to discuss how the urban names can be used to transform a urban space into a prestigious place by Fikirtepe example.
Keywords: Fikirtepe; urban toponymy; place names; Architecture